The Implementation of Traditional Game Media to Enhance Social-Emotional Relationships Between Elementary School Students - Ilmi, Samrotul; Julianto, Julianto; Kusmati, Ningsih Ari (CV. Publikasi Indonesia, 2024)
The research investigated using traditional gaming media to strengthen social and emotional connections among primary school students. The research focuses on enhancing values such as collaboration, understanding, and empathy through traditional games of choice. The method used is classroom action research with the active participation of grade 5 students of SDN Sidokare IV. Traditional children's play media was chosen as an intervention tool because it contains social values such as cooperation, communication, and empathy. Data were collected through participant observation, interviews, and questionnaires to assess changes in social-emotional interactions before and after the intervention. Data analysis was carried out using a qualitative approach. The results showed that consistent use of traditional game media can significantly improve the social-emotional connection of elementary school students and strengthen the level of empathy and understanding of elementary school students. This article provides a foundation for developing more effective strategies for building learning environments that support the development of positive social relationships.